(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In the evolving global economy, modern corporate management plays a critical role in the success and sustainability of large joint-stock companies with state participation. This annotation explores the significance of contemporary corporate governance practices in such enterprises, where state ownership introduces unique dynamics. Corporate management ensures that decision-making processes are transparent, efficient, and aligned with both business objectives and broader national economic goals. For state-owned or partially state-owned joint-stock companies, modern management practices help balance the interests of public shareholders, private investors, and the government, while promoting accountability and professionalism. Key aspects of modern corporate governance—such as board structure, executive management practices, performance monitoring, and stakeholder engagement—are essential in improving operational efficiency, fostering innovation, and enhancing competitiveness. In addition, compliance with regulatory standards and alignment with global corporate governance norms are crucial to building investor confidence and ensuring responsible management of public assets.